2020
DOI: 10.1111/1759-7714.13667
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of m6A reader YTHDC2 promotes tumor progression and predicts poor prognosis in non‐small cell lung cancer

Abstract: Background m 6 A modification affects the pathological progress of many diseases by affecting RNA stability and translocation. YTHDC2, a m 6 A reader, is associated with multiple cancers; however, little is known of its role in non‐small cell lung cancer (NSCLC). Methods The GEPIA, Oncomine and GEO databases were analyzed to assess expression of YTHDC2 in NSCLC patients. Quantitative polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In addition, knocking down hnRNPA2B1 can inhibit ESCA growth and metastasis ( Guo et al, 2020 ). In non-small cell lung cancer, down-regulation of the m6A reader YTHDC2 promotes tumor progression and predicts poor prognosis ( Sun et al, 2020 ). YTHDC2 activates the IGF1R/Akt/S6 signal axis to promote radiotherapy tolerance for nasopharyngeal carcinoma ( He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, knocking down hnRNPA2B1 can inhibit ESCA growth and metastasis ( Guo et al, 2020 ). In non-small cell lung cancer, down-regulation of the m6A reader YTHDC2 promotes tumor progression and predicts poor prognosis ( Sun et al, 2020 ). YTHDC2 activates the IGF1R/Akt/S6 signal axis to promote radiotherapy tolerance for nasopharyngeal carcinoma ( He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, low YTHDC2 expression was associated with poor prognosis in LUAD patients, and YTHDC2 improves the prognosis of LUAD patients by inhibiting the independent antioxidant function of SLC7A11 (Ma et al, 2021). In non-small cell lung cancer, a research analyzed a series of publicly available online databases and found that low YTHDC2 expression was associated with lymph node metastasis and poor prognosis (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We then reviewed the proteomic data and found YTHDC2 protein was reported significantly underexpressed in non-small cell lung cancer (Sun et al, 2020). The representative protein expression of ADH1C and YTHDC2 was explored in the human protein profiles and is shown in Figure 5B.…”
Section: External Validation Using Online Database About Genes In the Signaturementioning
confidence: 99%
“…In lung adenocarcinoma, it suppresses the tumorigenesis and development by inhibiting SLC7A11-dependent antioxidant function ( Ma et al, 2021 ). In non-small cell lung cancer, downregulation of m6A reader YTHDC2 promotes tumor progression and predicts poor prognosis ( Sun S. et al, 2020 ). YTHDC2 may promote the metastasis of colon cancer by promoting the translation of HIF-1α, and YTHDC2 may be a diagnostic marker and target gene for the treatment of colon cancer ( Tanabe et al, 2016 ).…”
Section: Rna M6a Modificationmentioning
confidence: 99%